French short stories : 30 French short stories for beginners to improve your French vocabulary - Moreau, Dylane (The Perfect French, 2023)
Do you struggle to find French reading material for beginners and intermediates? Look no further! Introducing French Short Stories! Improve your French with 30 easy French stories for beginners and intermediates. 30 short stories easily readable, covering everyday topics. The stories cover a variety of themes, including travel, friendship, family, and more. They are written in clear and concise language, making them easy to understand for beginners. The book also includes questions and answers for each story, allowing readers to test their comprehension and reinforce their understanding of the vocabulary. Read 1 story a day for 30 days and improve your French in only a month! French Short Stories has been written by a French teacher for French learners from beginner to intermediate level. Reading a story and answering the questions will take you less than 15 minutes a day."-- Provided by publisher